Genomic signals of local adaptation and hybridization in Asian white birch. Issue 3 (2nd December 2022) - Nocchi, Gabriele; Wang, Jing; Yang, Long; Ding, Junyi; Gao, Ying; Buggs, Richard J. A.; Wang, Nian
Abstract: Disentangling the numerous processes that affect patterns of genome‐wide diversity in widespread tree species has important implications for taxonomy, conservation, and forestry. Here, we investigate the population genomic structure of Asian white birch ( Betula platyphylla ) in China and seek to explain it in terms of hybridization, demography and adaptation. We generate whole genome sequence data from 83 individuals across the species range in China. Combining this with an existing data set for 79 European and Russian white birches, we show a clear distinction between B. pendula and B. platyphylla, which have sometimes been lumped taxonomically. Genomic diversity of B. platyphylla in north‐western China and Central Russia is affected greatly by hybridization with B. pendula . Excluding these hybridized populations, B. platyphylla in China has a linear distribution from north‐eastern to south‐western China, along the edge of the inland mountainous region. Within this distribution, three genetic clusters are found, which we model as long diverged with subsequent episodes of gene flow. Patterns of covariation between allele frequencies and environmental variables in B. platyphylla suggest the role of natural selection in the distribution of diversity at 7609 SNPs of which 3767 were significantly differentiated among the genetic clusters. The putative adaptive SNPs are distributed throughout the genome and span 1633 genic regions. Of these genic regions, 87 were previously identified as candidates for selective sweeps in Eurasian B. pendula . We use the 7609 environmentally associated SNPs to estimate the risk of nonadaptedness for each sequenced B. platyphylla individual under a scenario of future climate change, highlighting areas where populations may be under future threat from rising temperatures.